The Correlation Between Quality of Life and Positive Psychological Resources in Cancer Patients: A Meta-Analysis - Zhao, Xinxin; Tong, Siqi; Yang, Ye (Frontiers in Psychology, 2022)
Purpose This study aimed to assess the evidence of the association between positive psychological resources and quality of life in patients with cancer. Methods Electronic searching was performed to retrieve articles from PubMed, Web of Science, Embase, CNKI, and CBM (from inception to 7 April 2022). Summary correlation coefficient (r) values were extracted from each study, and 95% CIs were calculated by the random-effect model. Subgroup and sensitivity analyses were performed to investigate potential heterogeneity. Results In total, sixty-six articles were included in the present study. The pooled r for resilience was 0.71 (95%CI: 0.55, 0.87), hope 0.50 (95%CI: 0.43, 0.56), self-efficacy 0.53 (95%CI: 0.46, 0.61), self-esteem 0.46 (95%CI: 0.28, 0.63), and optimism 0.30 (95%CI: 0.19, 0.40). For subgroup analysis, no significant differences were found between minors and adults. Conclusion This study indicated that resilience, hope, optimism, self-esteem, and self-efficacy were positively correlated with quality of life in patients with cancers. Therefore, intervention programs should be focused on increasing state-like positive psychological resources to improve the quality of life in patients with cancer.